Earth Versus FIFA: Resisting Globalisation on the Open Pitch. (1st November 2022) - le Roux, Hannah
Abstract: Hannah le Roux is an architect and architectural historian specialising in the modern architecture of Southern Africa. An Associate Professor at the University of the Witwatersrand, here she documents the importance of football to local communities and its binding effect in strengthening societal bonds and providing a sense of self‐determination.